Modified Biering-Sorenson Protocol Changes Joint Contributions to Total Support in Individuals with a History of Anterior Cruciate Ligament Reconstruction During Drop Vertical Jump Landings - David M Werner; Maria F Mostaed; Samantha K Price; Joaquin A Barrios (North American Sports Medicine Institute, 2022)
# Background There are persistent deficits of the proximal musculature in individuals with anterior cruciate ligament reconstruction. Previous research has shown that proximal musculature fatigue alters drop vertical jump performance in healthy individuals. It is unknown how proximal musculature fatigue will alter drop vertical jump performance in individuals who have undergone anterior cruciate ligament reconstruction. # Hypothesis/Purpose The purpose of this study was to examine the effects of a proximal extensor musculature fatigue protocol on drop vertical jump landing biomechanics of individuals with a history of anterior cruciate ligament reconstruction using both single-joint parameters and total support moment analysis. # Study Design Quasi-experimental pre-post laboratory experiment # Methods Nineteen participants with a history of unilateral anterior cruciate ligament reconstruction were recruited. Three-dimensional motion analysis was performed bilaterally during a drop vertical jump. Participants then completed a proximal extensor musculature fatigue protocol and immediately repeated the drop vertical jump task. Sagittal plane kinetics and kinematics were collected. Joint contributions to peak total support moment were calculated. A condition-by-limb repeated measures analysis of variance was performed to explore the effects of the fatigue protocol, using an alpha level of 0.05. # Results There were no interactions observed for any parameters. However, the injured limb demonstrated less vertical ground reaction force (13%, p=0.013) and reduced peak dorsiflexion angle (2°, p=0.028) both before and after the protocol. After the fatigue protocol both limbs demonstrated reduced hip extensor contribution to peak total support moment (4%, p=0.035). # Conclusions Individuals with a history of anterior cruciate ligament reconstruction performed the drop vertical jump with an altered anti-gravity support strategy after the proximal extensor musculature fatigue protocol. The significant reduction in bilateral hip extensor contribution to peak total support moment suggests evidence of targeted fatigue. # Level of Evidence III